Insight stories: Looking into teacher support in enhancing scientific thinking skills among pre-school students - Latifah Binti Monnas (Journal of Educational Sciences, 2018)
Due to the revision of the National Pre-School Standard Curriculum (KSPK) 2017, the strengthening of Science and Technology Support and STEM integration early childhood education in Malaysia is now being aggressively developed in line with national education policies. This case study is conducted to find out how pre-school teachers apply science process elements in their teaching and learning activities. Observation was carried out on a pre-school teacher during a lesson in one of the national pre-schools in Tawau. Observation findings show that preschool teachers understand the need for  early science education though they lack the knowledge and application of the scientific skills. Therefore, it is highly recommended for pre-school teachers to improve appropriate pedagogical practices, and support the early process of science in early childhood education by contextually emphasizing and linking  their teaching to the 21st century curriculum.